2023
DOI: 10.1038/s41420-023-01427-9
|View full text |Cite
|
Sign up to set email alerts
|

MSI2 promotes translation of multiple IRES-containing oncogenes and virus to induce self-renewal of tumor initiating stem-like cells

Abstract: RNA-binding protein Musashi 2 (MSI2) is elevated in several cancers and is linked to poor prognosis. Here, we tested if MSI2 promotes MYC and viral mRNA translation to induce self-renewal via an internal ribosome entry sequence (IRES). We performed RIP-seq using anti-MSI2 antibody in tumor-initiating stem-like cells (TICs). MSI2 binds the internal ribosome entry site (IRES)-containing oncogene mRNAs including MYC, JUN and VEGFA as well as HCV IRES to increase their synthesis and promote self-renewal and tumor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Recent work has shown that MSI2 can bind to Internal Ribosome Entry Sites (IRES) located in the 5'UTRs of oncogenic mRNAs including MYC, JUN and VEGFA promoting protein expression by increasing translation. 14 Interestingly, LEF-1 also includes a potential IRES in its 5'UTR, 15 which coupled to our data suggest that MSI2 (together β-catenin) might bind the 5'UTR IRES of LEF1 to enhance its translation. This study further highlights novel roles for β-catenin in the RBP/RNA biology of haematopoietic cells which could be an important axis regulating human Toska, Lorraine Shah-Goodwin and Caroline Humphreys, for the collection of human umbilical cord blood.…”
supporting
confidence: 64%
“…Recent work has shown that MSI2 can bind to Internal Ribosome Entry Sites (IRES) located in the 5'UTRs of oncogenic mRNAs including MYC, JUN and VEGFA promoting protein expression by increasing translation. 14 Interestingly, LEF-1 also includes a potential IRES in its 5'UTR, 15 which coupled to our data suggest that MSI2 (together β-catenin) might bind the 5'UTR IRES of LEF1 to enhance its translation. This study further highlights novel roles for β-catenin in the RBP/RNA biology of haematopoietic cells which could be an important axis regulating human Toska, Lorraine Shah-Goodwin and Caroline Humphreys, for the collection of human umbilical cord blood.…”
supporting
confidence: 64%
“…RNA binding proteins (RBPs) can bind with transcript or non-transcript RNAs (11,12). In addition, eukaryotic translation initiation factor 4A3 (EIF4A3) is a member of RBPs, which is able to act as an oncogene in ESCA (13).…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) modulate expression patterns of various genes, which play important roles in different diseases. Several studies have unraveled associations between aberrant ncRNA expressions and pathologies of human diseases ( Singh et al, 2020 ; Yeh et al, 2023 ). Like other ncRNAs, recently discovered ncRNAs, circular RNAs (circRNAs) have also been found to play an important role in gene regulation via interaction with other biomolecules like nucleic acids, proteins, and microRNAs (miRNAs).…”
mentioning
confidence: 99%